PERAN GURU DAN ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN DARING DI SD NEGERI KARANGTOWO KABUPATEN DEMAK - Ayunita Hisbadina Tauqifa; Intan Rahmawati; Henry Januar Saputra (Universitas Negeri Medan, 2021)
Abstract:The Role of the teacher and parents in increasing student learning motivation in online learning at SD Negeri Karangtowo, Demak Regency. The purpose of this study was to find out how the role of teachers and parents in increasing student motivation and the results of student learning motivation in online learning at SD Negeri Karangtowo, Demak Regency. This type of research is a descriptive qualitative method. The sample in this study were 29 students of class VB. Data collection techniques used in this study were observation, interviews, documentation and questionnaires. The results of this study indicate that the teacher's role in motivating student learning includes the teacher as a demonstrator, the teacher as a class manager, the teacher as a mediator, the teacher as a facilitator, the teacher as an evaluator, and the teacher as a motivator. Meanwhile, the role of parents in motivating student learning includes parents as mentors or educators, parents as facilitators, and parents as motivators. And the results of the average student learning motivation showed 4% of students who said yes while 2% of students who said no. This the role of teacher and parents affect student learning motivation. Keywords: Teachers, Parents, Learning Motivation, Online Learning Abstrak: Peran Guru dan Orang Tua dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Daring di SD Negeri Karangtowo Kabupaten Demak. Tujuan penelitian ini untuk mengetahui bagaimana peran guru dan orang tua dalam meningkatkan motivasi belajar siswa dan hasil motivasi belajar siswapada pembelajaran daring di SD Negeri Karangtowo Kabupaten Demak. Jenis penelitian ini adalah metode kualitatif deskriptif. Sample dalam penelitian ini adalah 29 siswa kelas VB. Teknik pengumpulan data yang digunakan dalam penelitian ini berupa observasi, wawancara, dokumentasi dan angket. Hasil penelitian ini menunjukkan bahwa peran guru dalam memotivasi belajar siswa meliputi guru sebagai demonstrator, guru sebagai pengelola kelas, guru sebagai mediator, guru sebagai fasilitator, guru sebagai evaluator, dan guru sebagai motivator. Sedangkan peran orang tua dalam memotivasi belajar siswa meliputi orang tua sebagai pembimbing atau pendidik, orang tua sebagai fasilitator, orang tua sebagai motivator. Dan hasil rata-rata motivasi belajar siswa menunjukkan 4% siswa yang menyatakan ya sedangkan 2% siswa yang menyatakan tidak. Dengan demikian peran guru dan orang tua mempengaruhi motivasi belajar siswa.Kata Kunci: Guru, Orang Tua, Motivasi Belajar, Pembelajaran Daring